A new biodegradation drainage construction in surgical treatment of glaucoma - O. A. Kiseleva; A. N. Zhuravleva; E. A. Suleiman; K. V. Lugovkina (Российский офтальмологический журнал, 2018)
Reaching a prolonged hypotensive effect in the postoperative period is one of the main tasks of modern glaucoma surgery. The purpose of this work is to develop a new fully biodegradable drainage structure, made of domestically produced materials, and to use modified sinustrabeculectomy (STE) in the surgical treatment of primary open angle glaucoma (POAG) and refractory glaucoma. Materials and methods. The operation was performed in 27 patients (27 eyes) aged 50-70 (averagely 59.5 ± 1.9 years), who had been operated for POAG II (9 patients, 33.3 %) or POAG III (18 patients, 66.7 %) of staged b - c. For drainage, we used polyglycolic thread, which is an absorbable synthetic suture material. Complete absorption of drainage takes 60 to 90 days. The examination included standard methods (visometry, tonometry, computer perimetry, tonography, optic nerve HRT. In the early postoperative period optical coherence tomography of the anterior segment (ASOCT) was used, which was followed by ultrasound biomicroscopy (UBM). The follow-up period was up to 1 year. Results.1-3 months after the surgery, antihypertensive efficacy was noted in 100 % of cases (27 eyes), and 9-12 months after the surgery the figure was 98 % (26 of 27 eyes). Conclusions. The newly developed option of glaucoma surgery using a drainage structure made of domestically produced material provides a long-acting hypertensive effect // Russian ophthalmological journal. 2017; 10 (2): 36-9. doi: 10.21516/2072-0076-2017-10-2-36-39.